The Effect Of Mosaic Technique On Fine Motor Development In Preschool Children Aged 5-6 Years In TK Negeri Pembina 3 - Herlina, Sara; Sakinah, Sri Dewi; Hotmauli, Hotmauli (Jurnal Maternitas Kebidanan, 2025)
Background: Preschool age is the most important and fundamental early period throughout the growth and development span of human life. According to data from the WHO (World Health Organization), 5–25% of preschool-aged children suffer from minor brain dysfunctions, and 16% of children under five years old in Indonesia are found to have mild to severe neurological and brain development problems. Objective: To determine the effect of the mosaic technique on fine motor development in children aged 5–6 years at TK Negeri Pembina 3 in the year 2025. Method: This is a quantitative study using a quasi-experimental method with a one-group pretest-posttest design. The study was conducted in June 2025 at TK Negeri Pembina 3. The population of the study consisted of 23 children, and the sample consisted of 23 preschool-aged children (aged 5–6 years), selected using a total sampling technique. Data sources included both primary and secondary data. The research instruments used were SOPs and the Denver II Sheet. Data analysis techniques included univariate and bivariate analysis using the Wilcoxon test. Prior to the bivariate test, a normality test was conducted as a prerequisite. Results: The pretest results showed that the majority of 18 respondents or (78.3%) were in the delayed category. After the mosaic technique intervention, the posttest results showed that the majority of 16 respondents or (69.6%) were in the normal category. The Wilcoxon test showed a p-value of 0.000 < 0.05. Conclusion: There is an effect of the mosaic technique on the fine motor development of preschool children aged 5–6 years at TK Negeri Pembina 3.